Comprehensive Review of the Fundamental and Functional Properties of Crystalline Materials - T. B. Suneetha; R. M. Aadarsh Vel; R. Madhumitha Sri (International Journal of Crystalline Materials, 2026)
Crystalline materials, characterized by their highly ordered atomic arrangements, serve as the backbone of modern engineering and technology. This review provides a detailed examination of their diverse properties, categorized into mechanical, thermal, electrical, and optical domains. We analyze fundamental mechanical parameters such as the elastic modulus, yield strength, and fracture toughness, alongside functional behaviors like fatigue and creep. The discussion extends to thermal transport and expansion, electrical conductivity and resistivity, and advanced optical phenomena including piezoelectricity and nonlinear optics. By synthesizing recent advancements through 2026, this paper highlights the synergy between lattice symmetry and macroscopic performance. In addition, the role of crystallographic orientation and anisotropy is critically evaluated, as these factors significantly influence directional properties and performance under external stimuli. Defect engineering, including the manipulation of vacancies, dislocations, and grain boundaries, is discussed as a powerful strategy to tailor material behavior for specific applications. Recent progress in nanostructured and low-dimensional crystalline systems, such as thin films and quantum materials, has further expanded the functional capabilities of these materials. Moreover, advanced characterization techniques, including electron microscopy and synchrotron-based methods, have enabled precise insights into structure–property relationships at atomic and nanoscale levels. The integration of computational modeling and machine learning approaches is also emphasized, offering predictive capabilities for designing next-generation crystalline materials with optimized multifunctional properties for applications in electronics, energy storage, and photonics.
Keywords: Keywords: atomic arrangements; Piezoelectricity; aerospace; anisotropic properties; dielectric constant